Os sistemas serotonérgico, gabaérgico e endocanabinoide da amígdala medeiam a empatia relacionada à nocicepção em camundongos - Tavares, Ligia Renata Rodrigues (2020)
Evidence shows a reciprocal relationship between chronic pain and emotional disorders, exacerbating the other's experience. The affective-emotional component of pain can be activated not only in those who feel the pain but also in those who observe painful situations, characterized as empathy. In mice, living with chronic pain makes hypernociception, and the amygdala is one of the brain structures that play an essential role in emotional and nociceptive control. However, the neurotransmissions involved in this process are unknown. This study investigates the serotonergic, GABAergic, and endocannabinoid systems of the amygdala in mice's nociception empathy model. Male Swiss-albino mice were housed in pairs and, after 14 days of living together, one animal of the pair underwent sciatic nerve constriction surgery (constriction), or not (Sham) and returning to living with observers of the constriction [CNC (cagemate nerve constriction)] or Sham [CS (cagemate sham)], for another 14 days. On the 24th day, the CNC and CS groups underwent stereotactic surgery for bilateral cannula implantation in the amygdala. On the 28th day, the CNC and CS animals, after receiving ondansetron intra-amygdala injections (5-HT3 antagonist), mCPBG (5-HT3 agonist), (midazolam (GABAA-benzodiazepine agonist,) and cannabidiol (phytocannabinoid), were submitted to a nociceptive stimulus with acetic acid-induced writhing test [0.6% intraperitoneal (i.p.)]. The results reveal that living with chronic pain increased the expression of 5-HT3 receptors in the central and basolateral nuclei of the amygdaloid complex in both hemispheres. The administration of ondansetron (1.0 and 3.0 nmol), midazolam (3.0 and 30 nmol), and cannabidiol (30 nmol) reversed the hypernociception induced by cohabited together; and mCPBG (20 nmol) accentuated nociception in the CNC observer. Ondansetron (0.3 nmol, dose devoid of nociceptive effect), followed by midazolam or cannabidiol, reversed the antinociception produced by midazolam and cannabidiol, respectively, in mice after lived with a conspecific constrict. The results exhibit the involvement of the serotonergic, GABAergic, and endocannabinoid neurotransmissions of the amygdala and the interplay between these neurotransmissions in the hypernociception induced by the nociception empathy model.